Carbone or Oxygen Therapy: A Comparative Dosimetric Study Using PHITS Code - El Bekkouri, H.; Al Ibrahmi, E.; El-Asery, M.; Bardane, A.; El Mahjoub, C.; Didi, A.; Sadoune, Z. (Atom Indonesia, 2024)
Compared to conventional radiotherapy (X-rays or γ-rays), charged particle therapy shows more potential in treating deep-seated and radio-resistant tumors. Currently, all centers that offer hadron therapy use proton or 12C ion. Ongoing research is exploring the possibility of using others heavier ions, such as oxygen ion 16O or helium ion 4He. In this study, Monte Carlo method was used employing the Particle and Heavy Ion Transport code System (PHITS), to examine the amount of dose deposited by incident particles of 12C ion with energies of 200 and 300 MeV/u, as well as 16O ions with energies of 237.5 and 358.5 MeV/u. In this study, we investigated the depth dose distribution of carbon and oxygen ion beams by comparing their energy deposition in a water phantom and the impact of secondary particles. When considering lower energies, oxygen ions are more advantageous than carbon ions as they have slightly higher peak input ratios. This property enables higher doses to be delivered to tumor targets or lower doses to healthy surrounding tissues.